Adaptive Hypermedia and Adaptive Web-Based Systems 5th International Conference, AH 2008, Hannover, Germany, July 29 - August 1, 2008, Proceedings - Nejdl, Wolfgang; Kay, Judy; Pu, Pearl; Herder, Eelco (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2008)
This book constitutes the refereed proceedings of the 5th International Conference on Adaptive Hypermedia and Adaptive Web-Based Systems, AH 2008, held in Hannover, Germany in July 2008. The 24 revised full papers and 26 revised short papers presented together with abstracts of 3 keynotes, 4 demo papers, and 11 doctoral consortium posters were carefully reviewed and selected from 185 papers submitted. The papers focus on pioneering theories, techniques, and innovative technologies to provide dynamic personalization, adaptation, and contextualization of hypermedia resources and services.